Rethinking Therapeutic Strategies for Anorexia Nervosa: Insights From Psychedelic Medicine and Animal Models - Foldi, Claire J.; Liknaitzky, Paul; Williams, Martin; Oldfield, Brian J. (Frontiers in Neuroscience, 2020)
Anorexia nervosa (AN) has the highest mortality rate of any psychiatric disease, yet available pharmacological treatments are largely ineffective due, in part, to an inadequate understanding of the neurobiological drivers that underpin the condition. The recent resurgence of research into the clinical applications of psychedelic medicine for a range of mental disorders has highlighted the potential for classical psychedelics, including psilocybin, to alleviate symptoms of AN that relate to serotonergic signalling and cognitive inflexibility. Clinical trials using psychedelics in treatment-resistant depression have shown promising outcomes, although these studies are unable to circumvent some methodological biases. The first clinical trial to use psilocybin in patients with AN commenced in 2019, necessitating a better understanding of the neurobiological mechanisms through which psychedelics act. Animal models are beneficial in this respect, allowing for detailed scrutiny of brain function and behaviour and the potential to study pharmacology without the confounds of expectancy and bias that are impossible to control for in patient populations. We argue that studies investigating the neurobiological effects of psychedelics in animal models, including the activity-based anorexia (ABA) rodent model, are particularly important to inform best practice for clinical applications, including which subpopulations of patients may benefit most from psychedelic medicine.